2018
DOI: 10.1073/pnas.1701535115
|View full text |Cite
|
Sign up to set email alerts
|

Women live longer than men even during severe famines and epidemics

Abstract: SignificanceWomen live longer than men in nearly all populations today. Some research focuses on the biological origins of the female advantage; other research stresses the significance of social factors. We studied male–female survival differences in populations of slaves and populations exposed to severe famines and epidemics. We find that even when mortality was very high, women lived longer on average than men. Most of the female advantage was due to differences in mortality among infants: baby girls were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
152
2
9

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(182 citation statements)
references
References 87 publications
(104 reference statements)
9
152
2
9
Order By: Relevance
“…A longitudinal study conducted in Brazil reported that female suffered more from the loss of IADL than male, which was inconsistent with our ndings [23]. One reason was that female was generally more longevous than male, and the odds of IADL limitation was greater [46].…”
Section: Discussioncontrasting
confidence: 99%
“…A longitudinal study conducted in Brazil reported that female suffered more from the loss of IADL than male, which was inconsistent with our ndings [23]. One reason was that female was generally more longevous than male, and the odds of IADL limitation was greater [46].…”
Section: Discussioncontrasting
confidence: 99%
“…The results show that the risk for male babies is higher than that of female babies. This complies with the usual better survival outcome of the females as reports several manuscripts such as [34] or [35]. Multiple babies survive better than singleton babies; this is however against the results from studies conducted in Sub-Saharan Africa by Monden and Smits [36] and Pongou et al [37].…”
Section: Discussionsupporting
confidence: 87%
“…Second, the stronger associations of foetal and childhood exposure to famine observed in women than in men might be partly explained by mortality selection. It has been reported that men had higher mortality rates than women during famine . The body fat hypothesis has been proposed to explain sex differences in life expectancy .…”
Section: Discussionmentioning
confidence: 99%